2010
DOI: 10.1007/s10072-010-0396-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen cost of treadmill and over-ground walking in mildly disabled persons with multiple sclerosis

Abstract: Walking impairment is a ubiquitous feature of multiple sclerosis (MS) and the O2 cost of walking might quantify this dysfunction in mild MS. This paper examined the difference in O2 cost of walking between persons with MS who have mild disability and healthy controls and the correlation between the O2 cost of walking and disability. Study 1 included 18 persons with mild MS and 18 controls and indicated that the O2 cost of walking was significantly higher in MS than controls and that disability was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 14 publications
4
71
0
Order By: Relevance
“…In contrast, the PDDS score was not a significant predictor of gross-VO 2 , suggesting that it shared less variance with gross-VO 2 than the MSWS-12 score in the present participants. In support of this argument, PDDS scores have somewhat lower correlation with the oxygen cost per unit distance than MSWS-12 scores [21][22]. PDDS provides a single categorical rating of disease progression [19] and may be less sensitive or specific than the MSWS-12 scale in discriminating walking difficulties between persons with MS with minimal limitations such as the present participants.…”
Section: 1supporting
confidence: 50%
See 1 more Smart Citation
“…In contrast, the PDDS score was not a significant predictor of gross-VO 2 , suggesting that it shared less variance with gross-VO 2 than the MSWS-12 score in the present participants. In support of this argument, PDDS scores have somewhat lower correlation with the oxygen cost per unit distance than MSWS-12 scores [21][22]. PDDS provides a single categorical rating of disease progression [19] and may be less sensitive or specific than the MSWS-12 scale in discriminating walking difficulties between persons with MS with minimal limitations such as the present participants.…”
Section: 1supporting
confidence: 50%
“…The PDDS consists of a single item for measuring self-reported functional impairment, with particular focus on ambulation [19][20]. MSWS-12 and PDDS scores have been positively associated with the energetic cost of walking in persons with MS [21][22]. Both of these scales provide easily derived measures of walking impairment that could improve the accuracy of predicting gross-VO 2 during walking in persons with MS. More accurate prediction of gross-VO 2 may allow exercise professionals to design safer and more effective walking programs for managing symptoms and improving health in persons with MS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased gait variability has clinical significance in PwMS. Motl et al (2011) demonstrated that recurrent fallers (i.e. 1 + falls/year) with MS exhibit greater variability of spatial footfall placement than nonfallers with MS [30].…”
Section: Discussionmentioning
confidence: 98%
“…The participant then sat and rested quietly for 5 minutes. After the 5 minutes of rest, the participant undertook three 6-minute periods of walking; this period of walking is consistent with walking endurance protocols used for people with MS 8,9 and is of sufficient duration to achieve steady-state V…”
Section: Protocolmentioning
confidence: 97%
“…Some data indicate that walking impairment may affect accelerometer output and energy expenditure in populations with neurologic disorders. For example, one recent study found that walking impairment was strongly and significantly correlated with oxygen cost of walking across different speeds of treadmill and overground walking in people with MS. 9 Another study indicated that accelerometer output (ie, activity counts) was strongly and significantly associated with walking impairment in individuals with MS. 10 By extension, gait disability may moderate the association between energy expenditure and accelerometer output in people with MS. This would, in turn, indicate that the cut-point for quantifying time spent in MVPA from accelerometer output would vary between groups who differ in level of gait impairment.…”
Section: Gait Disabilitymentioning
confidence: 99%